2021
DOI: 10.1007/s12520-021-01461-7
|View full text |Cite|
|
Sign up to set email alerts
|

Use of meat resources in the Early Pleistocene assemblages from Fuente Nueva 3 (Orce, Granada, Spain)

Abstract: Over the last few decades, several types of evidence such as presence of hominin remains, lithic assemblages, and bones with anthropogenic surface modifications have demonstrated that early human communities inhabited the European subcontinent prior to the Jaramillo Subchron (1.07–0.98 Ma). While most studies have focused primarily on early European lithic technologies and raw material management, relatively little is known about food procurement strategies. While there is some evidence showing access to meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(75 citation statements)
references
References 121 publications
(152 reference statements)
4
70
1
Order By: Relevance
“…The comparison of tooth mark data with actualistic frameworks suggests that carnivore access to carcasses was likely secondary to hominins. This assessment, and the data presented in Yravedra et al (2021) for Fuente Nueva 3, are actually in agreement with the conclusions reached by Espigares et al (2019:10) for these Orce localities: 'carnivore activity in these sites seems to have been residual compared to hominin activity'.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The comparison of tooth mark data with actualistic frameworks suggests that carnivore access to carcasses was likely secondary to hominins. This assessment, and the data presented in Yravedra et al (2021) for Fuente Nueva 3, are actually in agreement with the conclusions reached by Espigares et al (2019:10) for these Orce localities: 'carnivore activity in these sites seems to have been residual compared to hominin activity'.…”
Section: Discussionsupporting
confidence: 92%
“…Barranco León (Guadix-Baza, Spain) is one of the oldest Early Pleistocene openair sites in Europe (1.4 Ma). This site, alongside the nearby locality of Fuente Nueva 3, presents evidence of hominin behaviour, including the earliest lithic assemblages documented in the Iberian Peninsula (Turq et al, 1996;Gibert et al, 1998;Barsky et al, 2010Barsky et al, , 2015Titton et al, 2019Titton et al, , 2020Titton et al, , 2021Toro-Moyano et al, 2009, 2010aYravedra et al, 2021). Barranco León has also produced hominin remains, specifically a mandibular left dm1 (Toro Moyano et al, 2013, although see also Gibert et al, 1999;Ribot et al, 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Over the years, specialists have pinpointed numerous flint outcrops and their detrital areas, also defining qualitative features (Toro-Moyano et al, 2007;Toro-Moyano et al, 2010, and references). During recent surveys we verified previously documented information; geo-localized significant findings; registered changes in environmental configurations, performed photographic documentation and collected lithic samples for experimental and didactic archeology (Barsky et al, 2018;Titton et al, 2018, Titton et al, 2020Yravedra et al, 2021). Experimental knapping/use contributes to knowledge about the mechanical qualities of the different kinds of stones found in the archeological samples.…”
Section: Surveyingmentioning
confidence: 53%
“…Early on, a dichotomous use of these two materials was made evident, with the limestone items being significantly larger-sized and the flint component marked most notably by the-typically Oldowan profile of small-sized cores and flakes ranging on average between only 2 and 3 cm in maximal length. Cut marks and traces of percussion observed on some of the large mammal remains from the two sites (Espigares et al, 2019;Yravedra et al, 2021) confirmed the use of small-sized flakes for cutting meat off of the large mammal carcasses in a presumably scavenger-type subsistence patterning and the issues of primary access to carcasses have been raised in relation to interaction among which there would also be episodes of competition with other large carnivores present coevally at the sites (Espigares et al, 2013;Yravedra et al, 2021). Compared with the relatively easy readability of the flint items, the limestone pieces present in the assemblages pose more interpretative difficulties, especially due to their highly non-standardized morphologies and also to the alteration of their weathered surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This article is a rebuttal to Yravedra et al (2021), who have recently published a reinterpretation of the taphonomy of the late Early Pleistocene archaeological site of Fuente Nueva 3 (FN3; Guadix-Baza Depression, SE Spain). In their paper, Yravedra et al (2021) challenge our previous inferences (Espigares et al 2013(Espigares et al , 2019 on the mode and time of access of sabretooth cats, hominins, and hyaenas to ungulate carcasses, favouring a model of primary access by the hominins to these resources.…”
Section: Introductionmentioning
confidence: 99%